Advances in the calibration of atom probe tomographic reconstruction - Gault, B; Moody, M; de Geuser, F; Tsafnat, G; La Fontaine, A; Stephenson, LT; Haley, D; Ringer, S (2009)
Modern wide field-of-view atom probes permit observation of a wide range of crystallographic features that can be used to calibrate the tomographic reconstruction of the analyzed volume. In this study, methodologies to determine values of the geometric parameters involved in the tomographic reconstruction of atom probe data sets are presented and discussed. The influence of the tip to electrode distance and specimen temperature on these parameters is explored. Significantly, their influence is demonstrated to be very limited, indicating a relatively wide regime of experimental parameters space for sound atom probe tomography (APT) experiments. These methods have been used on several specimens and material types, and the results indicate that the reconstruction parameters are specific to each specimen. Finally, it is shown how an accurate calibration of the reconstruction enables improvements to the quality and reliability of the microscopy and microanalysis capabilities of the atom probe. © 2009 American Institute of Physics.